P623 Colorectal cancer, colectomy rates and inflammatory bowel disease activity following liver transplantation in primary sclerosing cholangitis: a systematic review and meta-analysis. (25th January 2019) - Thomas, T; Cooney, R; Iqbal, T; Ghosh, S; Ferguson, J; Hirschfield, G; Trivedi, P
Abstract: Background: Primary sclerosing cholangitis (PSC) is the classical hepatobiliary manifestation of inflammatory bowel disease (IBD) for which liver transplantation [LT] is the only curative therapy. We provide pooled incidence rates (IR) and time trends of (1) colorectal cancer (CRC), (2) colectomy, and (3) IBD activity post LT through systematic review and meta-analysis. Methods: A systematic literature search of Medline and Embase was undertaken to identify studies that met the research objectives from 1981 to 2014. Studies were assigned to one or more of the three analytical streams (as above). The 'meta' package (R Studio (V.1.1.463)) and Revman was used to pool IRs and HRs from individual studies using a random effects model. Results: 42 studies were included in the systematic review. Twenty studies detailing the clinical course of 1994 patients (9874 patient-years) were pooled to assess the incidence of dysplasia or CRC (combined endpoint) and CRC only; IR 14.97 cases (95% CI 9.74–23.02) and 9.21(95% CI 6.01–14.09) per 1000 person-years, respectively. Heterogeneity was considerable ( I 2 = 86%). The incidence of post LT CRC was seen to be decreasing over time (Figure 1A). Time trends in the incidence of colorectal cancer and colectomy post LT in the PSC cohort. Colectomy following OLT was 23.18 per 1000 person-years (95% CI 16.74–32.08) ( I 2 = 84%).The IR for colectomy due to dysplasia/CRC was 11.25 cases per 1000 person-years (95% CI 6.43–19.68) and seen to be decreasing over time (Figure 1B). In contrast, worsening IBD activity necessitated colectomy in 13.26 cases per 1000 person-years (95% CI 9.95–17.66), with no change over time (Figure 1C). Nine studies reported clinical course of IBD post-LT according to endoscopy findings/escalation in IBD therapy. 27.6% of patients ( n = 584) experienced worsening IBD activity post LT. The effect of 5-aminosalicylates (5ASA) on risk of CRC (2 studies), colectomy (one study), and IBD activity (two studies) could not be analysed due to study heterogeneity. The effect of ursodeoxycholic acid (UDCA) on the risk of CRC after LT was examined by three studies. Due to data availability, only two studies could be pooled. UDCA increased the risk of CRC post LT; HR 2.90 (95% CI 1.37–6.11). The impact of UDCA on colectomy and IBD activity post-LT were inconclusive. No study examined biologics in context of study objectives. Conclusions: This is the first comprehensive systematic review and meta-analysis of IBD-related outcomes post LT in the PSC cohort. The risk of CRC mandates colonoscopy surveillance, although incidence appears to be decreasing. Identifying factors affecting IBD course is of critical importance, given that IBD deterioration appears to be the principal indication for colectomy post LT.